Decreased brain-derived neurotrophic factor serum concentrations in chronic post-stroke subjects (2016)
Background Brain-derived neurotrophic factor (BDNF) plays a critical role in sensorimotor recovery after a stroke. However, few studies have assessed the circulating BDNF levels in post-stroke humans to understand its changes. This study was conducted to measure BDNF serum concentrations in subjects with chronic hemiparesis, as well as to correlate serum concentrations with age, post-stroke time, total score of Stroke Specific Quality of Life Scale (SS-QOL), mobility subscale score, and motor function of SS-QOL. Methods Seventeen chronic post-stroke subjects matched by age and gender with healthy controls took part in the study. Personal data (age, hemiparesis side, and post-stroke time) were collected, and a physical examination (weight, height, body mass index) and SS-QOL assessment were carried out. On the same day, after the initial evaluation, venous blood samples were collected from the chronic post-stroke subjects and the healthy subjects. The BDNF serum concentrations were measured blindly by enzyme-linked immunosorbent assay. Results Subjects with chronic hemiparesis presented a decrease in BDNF serum compared with healthy subjects (P?<?.01). There was no correlation between BDNF serum levels with post-stroke time, age or quality of life, mobility, and the upper extremity motor function (P?>?.05). BDNF concentrations are related to structural and functional recovery after stroke; thus, this reduction is important to understand the rehabilitation process more clearly. However, more studies are needed considering the genetic variations and other tools to assess motor impairment and functional independence. Conclusion Chronic post-stroke subjects presented a decrease in BDNF serum concentrations, without a correlation with post-stroke time, age, and quality of life.